Interferential Electrical Stimulation Efficacy in the Management of Lower Urinary Tract Dysfunction in Children: A Review of the Literature - Sharifi-Rad, Lida; Ladi-Seyedian, Seyedeh-Sanam; Kajbafzadeh, Abdol-Mohammad (Urology Journal, 2021)
Background: Lower urinary tract dysfunction (LUTD) is the most common problem of the referral children to the pediatric urology clinics. If this condition does not treat early in life, it will be a lifelong problem. During recent decades, electrical stimulation therapy has been expanded and extensively used for the treatment of LUTD in both adults and children. The aim of this review is to suggest clinicians an updated understanding of effects of interferential (IF) electrical stimulation therapy in management of LUTD in children. Materials and methods: The search was performed in databases of Medline, PubMed, Google Scholar, ,and Scopus for information about IF electrical stimulation and its application using search words such as “ IF electrical stimulation”, “transcutaneous IF electrical stimulation” , “IF therapy ” , “ electrical stimulation”, “voiding dysfunction” , “ LUTD”, “ urinary incontinence” and “ children”. As this review focuses on the answer of this question “Does transcutaneous IF electrical stimulation has effect on management of LUTD in children?” we included the reference list of articles identified by this search strategy and selected those we judged relevant according to our keywords. Clinical trial studies that publishing in English were included. Categorical data were reported as frequencies and percentages. Results: Eleven studies were included in this review. The success rate of IF therapy in these studies has been reported from 61% to 90% of children with LUTD and urinary incontinence. Conclusion: IF electrical stimulation is an effective, safe and reproducible option to manage LUTD and urinary incontinence in children.